Visual Loss Caused by Central Retinal Artery Occlusion After Bee Sting: A Case Report - Su, Zhitao; Hu, Zhongli; Wang, Lei; Wang, Yao; Fang, Xiaoyun; Ye, Panpan (Frontiers in Medicine, 2021)
A bee sting can lead to an extremely rare case of visual loss caused by central retinal artery occlusion (CRAO). Here we report a 66-year-old healthy woman who was referred to our Eye Center because of visual loss which had occurred after bee sting two days earlier. The visual acuity was no light perception (NLP). Examination revealed left eyelid edema, conjunctiva congestion, a 6-mm fixed pupil, scattered retinal hemorrhage, and white-appearing ischemic retina with one small area of the normal-appearing retina temporal to the optic disk. Fundus fluorescein angiography revealed CRAO with one cilioretinal artery sparing. Her systemic workup revealed hypersensitivity, hypercoagulable state, myocardial damage and hepatic damage. After topical and systemic treatments, the visual acuity was still NLP with improved systemic workup. In brief, CRAO may occur after bee sting, and visual acuity should be monitored for early diagnosis.